2008
DOI: 10.1080/1937156x.2008.11949608
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Learning/Teaching Qualitative Research Approaches: An Ethnographic Autobiography

Abstract: The purpose of this paper is to use reflexive methodology to describe the emotions and experiences of doctoral students and a professor who collaboratively conducted a research study using triangulated qualitative research data. The study was the major learning strategy in a doctoral seminar focusing on qualitative research approaches. In using an ethnographic autobiography, the authors were the subjects of their own research. Data were examined from journals kept by the students and the instructor during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…Though not specific to doctoral workshops, similar findings were reported elsewhere (e.g., Leiper, Horn, Hu, & Upadhyaya, 2008). Additionally, doctoral seminar participants have reportedly enhanced their scholarly learning by risk taking, working together, and reflection (Henderson et al, 2008). Findings from the study of Dinkelman et al (2012) indicated that a doctoral seminar for future teacher educators help participants map the terrain of their research, prompt the topic of their research, learn a language for teacher education, value collaboration, and define purpose and care for the practice of teacher education.…”
Section: Structures and Benefitsmentioning
confidence: 96%
“…Though not specific to doctoral workshops, similar findings were reported elsewhere (e.g., Leiper, Horn, Hu, & Upadhyaya, 2008). Additionally, doctoral seminar participants have reportedly enhanced their scholarly learning by risk taking, working together, and reflection (Henderson et al, 2008). Findings from the study of Dinkelman et al (2012) indicated that a doctoral seminar for future teacher educators help participants map the terrain of their research, prompt the topic of their research, learn a language for teacher education, value collaboration, and define purpose and care for the practice of teacher education.…”
Section: Structures and Benefitsmentioning
confidence: 96%
“…The materials included visual sources like videos (Barrett, 2007), visual texts (photographs and drawings) (Davidson et al, 2009) practical and workshop exercises (Brandão, 2009;Harper et al, 2008;Healey-Etten & Sharp, 2010;Hein, 2004;Humphrey & Simpson, 2012;Roberts et al, 2013), assignments (Drisko, 2008), reflective journals (Hein, 2004;Koro-Ljungberg, Cavalleri, Covert, & Bustam, 2011;Reisetter, Yexley, Bonds, Nickels, & McHenry, 2003;Roulston et al, 2003), web-based instructional modules or learning objects (LOs) (Raddon, Raby, & Sharpe, 2009), using existing or publicly available data sets (Rogers, 2011), and problembased materials (Wiggins & Burns, 2009). A combination of practical materials has also been found useful (Forrester & Koutsopoulou, 2008;Henderson et al, 2008;Pratt & Dolbin-MacNab, 2003). The authors of the research articles identified numerous advantages of using these methods to teach qualitative research: Some of the challenges of using practical materials included the need for intensive support, the pressure of completing practical assessments in time, ensuring that students have the necessary theoretical background before embarking on practical applications, and class assignments not being as authentic as real-life research (Davidson et al, 2009;Hein, 2004;Humphrey & Simpson, 2012;Roberts et al, 2013;Rogers, 2011;Roulston et al, 2003;Wiggins & Burns, 2009).…”
Section: Theme 2: Practice-based Materialsmentioning
confidence: 99%
“…Talking about common challenges has been found to be helpful in these cases (Harper et al, 2008). Another disadvantage of working in groups is the need to reconcile different backgrounds and viewpoints (Henderson et al, 2008). Some students found it difficult to work in a large (such as eight-member) group instead of having the freedom to conduct their own studies and would have preferred smaller teams to enhance group cohesiveness and make it easier to find time for everyone to meet to discuss their progress (Sidell, 2007).…”
Section: Theme 4: Peer or Collaborative Workmentioning
confidence: 99%
See 2 more Smart Citations